Acupuncture improves the symptoms, gut microbiota, metabolomics, and inflammation of patients with chronic obstructive pulmonary disease: a multicenter, randomized, sham-controlled trial protocol - Liu, Yilin; Luo, Qin; Li, Junqi; Yang, Chunyan; Huang, Fengyuan; Xu, Guixing; Liang, Fanrong (Frontiers in Medicine, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is a common chronic respiratory disease. The occurrence of COPD is associated with gut microbiota, meticulous metabolism and inflammation. Acupuncture may be effective as an adjunctive therapy for COPD, but the available evidence is limited. This study aims to confirm whether acupuncture therapy has an adjunctive therapeutic effect on COPD and to investigate the relationship between the efficacy and the gut microbiota, metabolomics and inflammation.MethodsThis study is a multicenter randomized controlled trial. A total of 72 patients with stable COPD eligible will be randomized in a 1:1 ratio to receive either manual acupuncture (MA) or sham acupuncture (SA) without puncturing the skin. There will be no changes to the essential medicines used for all patients. The intervention will be 12 weeks, 3 times per week and follow-up will be 52 weeks. The primary outcome will be the change in COPD Assessment Test (CAT) score before and after treatment. Secondary outcomes will include modified Medical Research Council (mMRC), St. George’s Respiratory Questionnaire (SGRQ), 6-min walk test (6MWT), and the number of moderate or severe acute exacerbations during follow-up. A total of 36 healthy volunteers will also be recruited as normal control. In addition, feces and blood will be collected from each participant to characterize the gut microbiota, metabolomics, immune cells and inflammatory cytokines. Differences between COPD patients and healthy participants will be observed, as well as changes before and after treatment in MA and SA groups. Ultimately, the correlation among gut microbiota, metabolomics, immune cells, inflammatory cytokines and clinical efficacy in COPD patients will be analyzed.DiscussionThis study will evaluate the efficacy and provide preliminary possible mechanisms of acupuncture as an adjunctive therapy in treating COPD. In addition, it will identify biomarkers of the gut microbiota, metabolites, immune cells, and inflammatory cytokines associated with therapeutic efficacy. The results of this study will be published in a peer-reviewed journal.